Land Revenue and Agrarian Economy - Umadevi Rajareddy, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
Land revenue policies play a crucial role in shaping agrarian economies, influencing farmers' livelihoods, and determining agricultural productivity. This paper provides a critical review of the relationship between land revenue policies and agrarian economics, highlighting the challenges and opportunities in promoting sustainable agricultural practices and rural development. By examining existing literature and case studies, this review aims to contribute to a deeper understanding of the complex interactions between land revenue systems, agricultural productivity, and rural economies, ultimately informing policy decisions that support sustainable agricultural development and equitable economic growth.
Keywords: Land Revenue; Agrarian Economics; Agricultural Productivity; Rural Development; Policy Design